Incidencia de la práctica de la danza y folklore para la potencialización de valores cívicos en los estudiantes de la carrera de Cultura Física de la Facultad de Ciencias Sociales de la Universidad Técnica de Machala en el período lectivo 2012-2013. - Urdiales Prieto, María Mercedes (2016)
This research reveals the deficiency in the practical development and diffusion of civic values ​​in daily life, work and education in students of the race of Physical Culture, this lack limits the integral development of the future professional, since we must take Considering that in the future he will work with children and adolescents, thus becoming a potential transmitter of values. One of the reasons for this limitation is that the university teacher currently only focuses on the transmission of content and development of knowledge of the subjects of the study curriculum in force, leaving aside something primordial in the development of the integral of the student in process Of vocational training is to promote the practice of civic values. It takes into consideration the subject of dance and folklore since its contents are suitable for the transmission of civic values ​​through representations of everyday life, for its richness in body expression, for transmitting facts of our own identity that allow us to keep our own lives alive Culture and lay the foundations for future generations.